2012
DOI: 10.4028/www.scientific.net/kem.520.1
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Ti PM: Progress, Opportunities and Challenges

Abstract: Utilization of titanium components made by powder metallurgy methods has had limited acceptance largely due to the high cost of titanium (Ti) powder. There has been renewed interest in lower cost economical powders and several Ti reduction methods that produce a particulate product show promise. This talk summarizes work done at Oak Ridge National Laboratory to consolidate these economical powders into mill products. Press and sinter consolidation, hot isostatic pressing (HIP) and direct roll consolidation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…There are many potential applications of titanium and titanium alloys requiring lower but reproducible levels of mechanical properties. For this reason, Peter et al suggested that an industrial grade of titanium and titanium alloys should be developed, which can provide adequate levels of properties to fulfil the obligation of less demanding components rather than manufacturing of these parts from non-feasible aerospace-quality material [17]. Based on this principle, the present study explores the processing of Ti-6Al-4V alloy prepared from starting powders with relatively high oxygen contents.…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential applications of titanium and titanium alloys requiring lower but reproducible levels of mechanical properties. For this reason, Peter et al suggested that an industrial grade of titanium and titanium alloys should be developed, which can provide adequate levels of properties to fulfil the obligation of less demanding components rather than manufacturing of these parts from non-feasible aerospace-quality material [17]. Based on this principle, the present study explores the processing of Ti-6Al-4V alloy prepared from starting powders with relatively high oxygen contents.…”
Section: Discussionmentioning
confidence: 99%
“…The process yields a crude product encapsulated in LiCl and, depending on whether the metallothermic reduction is completed with a stoichiometric excess of Li or TiCl₄, may also contain traces of excess Li, TiCl₃, and TiCl₂. These residual reaction byproducts are detrimental to the mechanical characteristics of manufactured products (Peter et al, 2012): chlorides are volatile at high temperature, resulting in macro-porosity, which degrades fatigue properties (Yan, Tang, and Qian, 2015), while oxygen changes phase selection and microstructure, which increases the elastic modulus and yield strength, but reduces ductility (Baril, Lefebvre, and Thomas, 2011). The challenge encountered in most alternative methods to produce titanium powder is the economic removal of byproducts to achieve the target titanium specification (Liang et al, 2018;Peter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys exhibit an exclusive combination of distinct properties such as low density, good corrosion resistance, and biocompatibility (Oosthuizen, 2011;van Vuuren, Oosthuizen and Heydenrych, 2011;Froes, 2012;Fang et al, 2018).These properties are required to produce longer life components capable of mitigating environmental problems (Hansen and Gerdemann, 1998). However, the high cost of titanium and its alloys compared to competing materials like stainless steel and aluminium limits their widespread use in the full range of potential applications (Froes and Ashraf Imam, 2010;Oosthuizen, 2011;van Vuuren, Oosthuizen, and Heydenrych, 2011;Peters et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the fine grain size possible with this method enhances mechanical properties and makes it possible to engineer unique alloy combinations that may not be possible with conventional ingot metallurgy (Fang et al, 2018). Despite these advantages, titanium PM is currently limited to niche applications due to the unavailability of lowcost quality powder (Froes and Ashraf Imam, 2010;Peters et al, 2012).…”
Section: Introductionmentioning
confidence: 99%